IMPLEMENTASI KEGIATAN EKSTRAKURIKULER PRAMUKA DALAM PEMBINAAN KARAKTER SISWA MADRASAH IBTIDAIYAH RAUDLATUL ULUM NGIJO KARANGPLOSO MALANG - Asri Yani Arkiang; Rosichin Mansur; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The progress of people's lives in a country is strongly influenced by progress of education in the world in this basic education has the very role building in the personality and character   2. To describe the implementation of scout extracurricular activities in fostering student character Ibtidaiyah Madrasah Raudlatul Ulum Ngijo Karangploso Malang, 3. Describing the supporting and inhibiting factors for the implementation of activities scout extracurricular activities in the formation of a student's musical character in the Raudlatul Ulum Ngijo Islamic School in Malang.